Pengendalian hama penggerek ubi jalar Cylas formicarius (Fabricus) (Coleoptera: Curculionidae) menggunakan cendawan entomopatogen Beauveria bassiana (Balsamo) Vuillemen - Marida Santi Yudha Ika Bayu; Yusmani Prayogo (Jurnal Entomologi Indonesia, 2016)
Cylas formicarius (Fabricus) (Coleoptera: Curculionidae) is one of the major pest on sweetpotato which can cause yield lost up to 100%. The objective of this study was to obtain the effective and efficiency control technique of sweetpotato weevils. The research was conducted on June–October 2014 at Muneng Research Station, Probolinggo, East Java, using randomized block design, five treatments and three replicates. The treatments consisted of immersion of sweetpotato cuttings in the suspension of conidia Beauveria bassiana (Bals.) Vuill. for 30 minutes before planting; application of suspension of conidia B. bassiana on soil at 2, 4, 6, 8, 10, and 12 weeks after sowing (WAS); immersion of sweetpotato cuttings in the suspension of conidia B. bassiana for 30 minutes before planting combined with application of suspension of conidia B. bassiana on soil at 2, 4, 6, 8, 10, and 12 WAS; application of chemical insecticide every week; and control. Analysis of variance showed that the application of various control technique significantly lowered the population of larvae and imago of C. formicarius and the level of tuber damage. The population level found on all treatments ranged from 1–4 eggs/plant, 1–19 larvae/plant, 0–0.2 pupae/plant and 0–4 imago/plant. The weight of tuber was 571–700 g/plant with the level of damage 6–53%. Low level of damage was found in the aplication of suspension of conidia B. bassiana on soil at 2, 4, 6, 8, 10, and 12 WAS which were 6%. Application of suspension of conidia B. bassiana on soil at 2, 4, 6, 8, 10, and 12 WAS can suppress the population of C. formicarius on tuber and reduce the level of damage up to 48%.